Digital Literacy and Intention to Adopt E-Government (a Survey of Regional Inspectorate Employee in South Sumatra Province) in 2023 - Firanda Meitania; Azhar; Alamsyah (LP2M IAIN Palopo, 2025)
This research aimed to analyze and determine employees' digital literacy and intention to adopt e-government at the regional inspectorate of South Sumatra Province. This study used perceived usefulness and perceived ease of use as intervening variables that influence an individual's intention to adopt e-government or not, either directly or indirectly. The research employed a quantitative method with data analyzed using SmartPLS version 3. Data were collected by distributing questionnaires to 80 employees of the Regional Inspectorate of South Sumatra Province using simple random sampling, and responses were measured on a Likert scale. The results indicated that digital literacy did not significantly affect the intention to adopt e-government. However, digital literacy influenced perceived usefulness, which in turn affected the intention to adopt e-government. Additionally, digital literacy affected perceived ease of use, and perceived ease of use influenced the intention to adopt e-government. Ultimately, digital literacy impacted the intention to adopt e-government through perceived usefulness and perceived ease of use.